Talking with Sellars about rules - Heck, Ralph Leal; Brito, Carlos Eduardo Fisch de (Argumentos - Revista de Filosofia, 2024)
Sellars poses the questions, "What is language?" and "How do we learn language?" and sets out to answer them. But these questions are very interesting, and we want to answer them too. This gives rise to our conversation, which resembles a meeting of two people talking to themselves — (like any other conversation). Thus, the two stories unfold in parallel, at times converging and at times diverging. But it never fully resolves. This is because Sellars has in mind the descriptive paradigm of language, while we want to discuss the prescriptive paradigm. Once this becomes clear, we set Sellars aside and begin outlining our notes for a prescriptive semantics of language.